Clarifying the Distinction Between Malignant Peripheral Nerve Sheath Tumor and Dedifferentiated Liposarcoma: A Critical Reappraisal of the Diagnostic Utility of MDM2 and H3K27me3 Status. (May 2018) - Makise, Naohiro; Sekimizu, Masaya; Kubo, Takashi; Wakai, Susumu; Hiraoka, Nobuyoshi; Komiyama, Motokiyo; Fukayama, Masashi; Kawai, Akira; Ichikawa, Hitoshi; Yoshida, Akihiko
Abstract : Malignant peripheral nerve sheath tumor (MPNST) and dedifferentiated liposarcoma (DDLPS) are 2 major types of pleomorphic spindle cell sarcoma. The differentiation of MPNST and DDLPS by histomorphology alone can be problematic. Although MDM2 amplification and PRC2 alteration leading to H3K27me3 deficiency are genetic hallmarks of DDLPS and MPNST, respectively, a small number of MDM2 -amplified MPNSTs and H3K27me3-deficient DDLPSs have been reported in the literature. We systematically compared MDM2 and H3K27me3 status in 68 MPNSTs and 47 DDLPSs. Of the 62 MPNSTs, 22 were immunopositive for MDM2, mostly in a weak and/or focal manner. Of the 21 MDM2-positive MPNSTs successfully tested by fluorescence in situ hybridization, high-level MDM2 amplification was observed in 1 case. In contrast, MDM2 staining and high-level MDM2 amplification were positive in all the DDLPS tested (28/28 and 20/20). Of the 68 MPNSTs, 42 cases (62%) exhibited complete loss of H3K27me3. All the 13 MPNSTs that showed heterologous differentiation were deficient in H3K27me3. Of the 47 DDLPSs, 3 cases (6%) had complete loss of H3K27me3, all of which exhibited heterologous differentiation. One case of H3K27me3-deficient DDLPS exhibited homozygous loss of EED according to targeted next-generation sequencing, whereas there were no alterations in NF1 and CDKN2A . In conclusion, high-level MDM2 amplification strongly suggests DDLPS over MPNST. Although a good marker for MPNST, H3K27me3 deficiency also uncommonly occurs in DDLPS in association with PRC2 mutational inactivation. Because both markers are imperfectly specific, rare sarcomas with dual features could be encountered, and their classification should integrate other parameters. Abstract : Supplemental Digital Content is available in the text.